Legal Certainty of PPJB Land Objects Certificate Issued on The Basis of Breach of Performance (Study of Decision Number 236/PDT. G/2022/Pn.TJK) - Eferdy, Faiza; Nurlela, Nurlela; Samosir, Tetti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
PPJB is an agreement between the seller and the buyer before the sale and purchase is carried out because there are elements that must be met for the sale and purchase. The problems in this study were analyzed using normative methods with qualitative analysis to obtain conclusions about Certificate Position Ownership Rights No. 00882 dated September 9, 2022 covering an area of 1,657 m2 (one thousand six hundred and fifty seven square meters) is invalid and can be canceled due to administrative legal defects, cancellation or an order to record changes to the maintenance of land registration data can be made according to laws and regulations. Administrative legal defects occur due to errors in: procedures in the process of determining and/or registering land rights; procedures in the process of registering transfers of rights and/or replacement certificates; procedures in the process of registering confirmation and/or recognition of rights to land formerly owned by customary law; procedural errors in the process of measuring, mapping and/or calculating the area; overlapping rights or land rights certificates; errors in the subject and/or object of rights; and other errors in the application of laws and regulations.